Correction: Local versus Generalized Phenotypes in Two Sympatric Aurelia Species: Understanding Jellyfish Ecology Using Genetics and Morphometrics. - Luciano M Chiaverano; Keith M Bayha; William M Graham (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0156588.].